Potensi dan Kendala Program Wajib Belajar Sembilan Tahun di Pesantren : Kasus di Kabupaten Bangkalan - Titik Handayani (Badan Litbang dan Diklat Kementerian Agama RI, 2008)
This article will expose the potency and constraint faced by pesantren (Islamic boarding school) in policy implementation of Program Wajar Dikdas Sembilan Tahun (Nine Years Basic Education Program) in regency of Bangkalan, East Java, considering that the education in Bangkalan, Madura generally either quantitatively is still pertained â€œlowâ€ if compared with education in East Java in general. Though, administratively Bangkalan, Madura Island included into east Java Province and geographically Bangkalan abuts with the second metropolitan town that is Surabaya. Even, East Java Province will specify the policy of twelve years basic education program untul senior high school level.